The role of the charitable funds iniciated by people’s deputies of ukraine from volyn in the development of the region - Mirchuk, Ilona S.; Мірчук, Ілона Сергіївна (London University Press, 2014)
The article considers the main forms and aspects of charity fundraising activity. In the focus of attention is the implementation of charity funds projects. The article lays emphasis on the importance and benefits of the charity fundraising models initiated by the People’s deputies of Ukraine from Volyn region.

У статті здійснено аналіз основних напрямків діяльності благодійних фондів. Проаналізовано реалізацію проектів фондів, відповідно до поставлених завдань. Досліджено роль благодійних фондів народних депутатів України від Волинської області у розбудові краю.
Роль благодійних фондів народних депутатів України від Волинської області у розбудові краю
Keywords: People’s deputy of Ukraine; charity fund; civil society; development of the region; social initiatives; development projects; благодійність; народний депутат України; благодійний фонд; громадянське суспільство; розбудова краю; соціальні ініціативи; програма розвитку